CBT Exam Implementation Guidance for Students in Facing Digital-Based Assessments - Annisa Tri Ananda Dewi; Moh Rofik; Moh Holidi; Najiburahman Najiburahman; Hasan Baharun; Abdul Wahid Zaini; M Aqil Fahmi Sanjani (Communautaire: Journal of Community Service, 2025)
The development of digital technology necessitates a transformation in learning evaluation systems in schools, including at the junior high school level; however, many schools still rely on manual, paper-based examinations, resulting in limited student experience and insufficient digital readiness to face computer-based assessments. This condition potentially hinders students’ ability to adapt to national computer-based assessments. This Community Service activity aimed to implement Computer-Based Test (CBT)–based examinations to improve students’ digital readiness while enhancing the effectiveness and efficiency of learning evaluation in junior high schools. The implementation employed a participatory approach using the Action–Plan–Analyze–Reflect (APAR) strategy, which included needs analysis, planning, action through socialization, simulations, and CBT exam implementation, as well as reflection and evaluation involving teachers and students. The results demonstrated a significant improvement in students’ digital readiness, as indicated by their ability to operate the examination system independently, increased self-confidence, and better understanding of digital device usage. In addition, the implementation of CBT benefited teachers and schools by reducing correction time, minimizing paper usage, and simplifying the management of examination result data. The program activity contributes positively to the digital transformation of learning evaluation and serves as an applicable and sustainable model for CBT implementation in junior high school settings.